Humanized chimeric uPA mouse model for the study of hepatitis B and D virus interactions and preclinical drug evaluation - Lütgehetmann, Marc; Urban, Stephan (Hepatology, 2012)
No specific drugs are currently available against hepatitis delta virus (HDV), a defective virus leading to the most severe form of chronic viral hepatitis in man. The lack of convenient HDV infection models has hampered the development of effective therapeutics. In this study, naïve and hepatitis B virus (HBV) chronically infected humanized uPA/SCID mice were employed to establish a small animal model of HBV/HDV coinfection and superinfection. For preclinical antiviral drug evaluation, the GMP version of the myristoylated preS-peptide (Myrcludex-B), a lipopeptide derived from the pre-S1 domain of the HBV envelope, was applied to prevent de novo HBV/HDV coinfection in vivo. Virological parameters were determined at serological and intrahepatic level both by real-time polymerase chain reaction (PCR) and by immunohistochemistry. Establishment of HDV infection was highly efficient in both HBV-infected and naïve chimeric mice with HDV titers rising up to 1 × 10E9 copies/mL. Notably, HDV superinfection led to a median 0.6log reduction of HBV viremia, which although not statistically significant suggests that HDV may hinder HBV replication. In the setting of HBV/HDV simultaneous infection, a majority of human hepatocytes stained HDAg-positive long before HBV spreading was completed, confirming that HDV can replicate intrahepatically also in the absence of HBV infection. Furthermore, the increase of HBV viremia and intrahepatic cccDNA loads was significantly slower than in HBV mono-infected mice. Treatment with the HBV entry inhibitor Myrcludex-B, efficiently hindered the establishment of HDV infection in vivo. Conclusion: We established an efficient model of HBV/HDV infection to exploit mechanisms of viral interference in human hepatocytes and to test the efficacy of an HDV-entry inhibitor in vivo. (HEPATOLOGY 2011)
Published online: 26 October 2011
Gesehen am 11.05.2018